Improving rural public health through 'best practice' water, sanitation and hygiene initiatives. (March 2019) - Bowling, Tari; Hall, Nina
An understanding of best practice rural water, sanitation and hygiene (rWASH) and its associated indicators can ensure greater success and reduced failure of future projects. While numerous organisations have actively implemented rWASH projects since the early 1990s with donor reports, funding proposals and reviews frequently claiming best practice, there remains a paucity of information on what constitutes 'best practice' rWASH. A scoping review of qualitative and quantitative literature was done with six primary factors identified as key contributors to best practice rWASH: regulatory environment, community ownership, programme methodology, funding, technology and capacity. In the absence of standardisation, a benchmark of proven techniques may be used as an alternative to identify 'best practice' within the sector and propose minimum requirements for the development of best practice rWASH. Clearly defining best practice rural water, sanitation and hygiene is useful for governments, donor agencies and implementing organisations and those monitoring outcomes of programmes against national and global targets.